Ombre de Solitude ou l’héroïsme en négatif dans La Mulâtresse Solitude d’André Schwarz-Bart - Odile Hamot (Études Caribéennes)
This study aims to analyse the heroine of André Schwarz-Bart’s novel, A Woman named Solitude. In this novel, the author makes the disconcerting choice to settle a character not only far from the image of the strong, rebellious and exemplary woman the people of Guadeloupe made her out, but also who shows the deconstruction of heroism. It will be interesting to explore the ways and the meanings of this redefinition of heroism in terms of literature and philosophy.